Digital Consumer Engagement: Examining the Impact of Audio and Visual Stimuli Exposure in Social Media - Dina Mardhatilah; Azizah Omar; Ramayah Thurasamy; Rosa Prafitri Juniarti (Information Management and Business Review, 2023)
The promotion of coffee shops through Instagram content has become highly beneficial to consumers’ decision-making, as short videos reel Instagram and photos can help consumers judge and experience products through visual and audio stimuli on content. Consequently, scholars and managers must understand consumer behaviors regarding audio-visual stimuli on Instagram content and identify factors influencing perception and consumer engagement with content. A novel contribution of this study is the introduction of audio-visual stimuli on Instagram content based on the stimulus-organism-response paradigm, which explains how sensory marketing and information adoption affect consumer engagement on social media Instagram. To empirically evaluate the proposed research model, we conducted an online survey with 120 participants who followed Instagram @kopijanjijiwa and @kopikenangan. We performed data analysis using structural equation modelling and Smart-PLS software and the results indicated that all hypotheses, except for perceived cognitive and audio-visual stimuli, significantly affected consumer engagement. This study could provide insights into the antecedents of perceived cognitive and consumer engagement on social media Instagram. Thus, contributing knowledge of digital consumer behavior helps managers understand consumer behavior regarding social media and formulate marketing strategies.